zk‐STARKs based scheme for sealed auctions in chains - Li Wei; Liang Peili; Li Fei (IET Blockchain)
Abstract On‐chain sealed auctions represent a novel approach to electronic bidding auctions, wherein the introduction of zero‐knowledge proof technology has significantly enhanced the security of auctions. However, most mainstream on‐chain sealed auction schemes currently employ Bulletproofs to prove auction correctness, which leaves room for optimization in terms of verification time and inherent security. Addressing these issues, an on‐chain sealed auction scheme based on zero‐knowledge succinct non‐interactive argument of knowledge (zk‐STARK) is proposed. This scheme leverages the decentralization and immutability of blockchain and smart contracts to eliminate third‐party involvement while ensuring the security of the auction process. The Inter Planetary File System is utilized to provide a qualification review mechanism for the auctioneer, enabling the screening of unqualified bidders before the auction. Additionally, the scheme employs RSA encryption to conceal bidders' bids, Pedersen commitments to ensure the consistency of bidding information, and zk‐STARKs to verify the correctness of the winning bid. Security analysis and experimental results demonstrate that the proposed scheme meets the required security standards, with time consumption at various stages of the auction being within acceptable limits, and effectively reduces the time required for proof verification.